EFFECTS OF ORGANIC PLANT EXTRACTS ON BEHAVIOR OF Sitophilus zeamais MOTS. (COLEOPTERA: CURCULIONIDAE) ADULTS - Prado Ribeiro, Leandro; Vendramim, JosÃ© Djair (REVISTA DE AGRICULTURA, 2017)
The aim of the present study was to evaluate the action of organic plant extracts from different parts of some species on host selection behavior of Sitophilus zeamais (Coleoptera: Curculionidade) adults. With the exception of extracts prepared from Aristolochia paulistana, all other tested plant extracts showed effect on behavior of S. zeamais adults, depending on concentration and solvent used in their preparation. The most pronounced repellent and/or deterrent effects were obtained with nonpolar extracts (in hexane and dichloromethane) of Annona montana, Annona mucosa, and Casearia sylvestris. On the other hand, ethanolic extracts from branches of C. sylvestris, leaves of A. montana, and leaves and seeds of A. mucosa were attractive and/or stimulant of feeding and/or oviposition of S. zeamais adults, depending on the concentration used. Thus, these extracts are promising sources of attractive compounds to be used in food baits in monitoring traps or even as repellents of stored grain pests.Â Â